A comparison study of the Structural and magnetic properties of pure Ni metal and NiZnMn ferrite - Al-Hilli, Muthafer F. (Iraqi Journal of Physics, 2019)
The magnetic properties of a pure Nickel metal and Nickel-Zinc-Manganese ferrites having the chemical formula Ni0.1(Zn0.4Mn0.6)0.9Fe2O4 were studied. The phase formation and crystal structure was studied by using x-ray diffraction which confirmed the formation of pure single spinel cubic phase with space group (Fd3m) in the ferrite. The samples microstructure was studied with scanning electron microstructure and EDX. The magnetic properties of the ferrite and nickel metal were characterized by using a laboratory setup with a magnetic field in the range from 0-500 G. The ferrite showed perfect soft spinel phase behavior while the nickel sample showed higher magnetic loss and coercivity.